Structured manipulable material versus applet in the development of algebraic thinking at the 1st cycle of basic education - Santos, Nuno (2018)
Submitted by Isabel Goulão (isabel.goulao@ipcb.pt) on 2018-02-01T10:59:56Z No. of bitstreams: 1 2-Structured.pdf: 767496 bytes, checksum: 43befd920d131ed91f8e41cfde9e6889 (MD5)